The Effect Of Service Quality Perception And Company Image On Customer Satisfaction And Their Impact On Customer Loyalty Indihome - Puspasari, Aprilia; Nurhayaty, Ety; Riftiasari, Dinar; Yuniarti, Puji; Suharyadi, Dedi; Martiwi, Rini; Adawia, Popon Rabia; Baharuddin (IJOSMAS, 2022)
This study aims to examine and analyze the effect of perceived service quality and corporate image on satisfaction and its impact on Indihome customer loyalty. Data collection was carried out on Indihome customers in Jakarta, Bogor, Depok, Tangerang and Bekasi, using email and google forms during November 2021 for 125 respondents. The research was carried out in the form of field research, using the Simple Random Sampling technique, namely the sampling was carried out randomly without regard to the existing strata in the population. The data collected was analyzed using Structural Equation Modeling with SmartPLS version 3.0 software. The results showed that the perception of service quality was not significant to customer satisfaction, corporate image had a significant effect on customer satisfaction, perceived service quality had a significant effect on customer loyalty, corporate image had a significant effect on customer loyalty, customer satisfaction had a significant effect on customer loyalty, and customer satisfaction significantly mediated influence of Service Quality Perception and corporate image on Customer Loyalty.